Self-referential schemas and attentional bias predict severity and naturalistic course of depression symptoms. Issue 4 (19th May 2017) - Disner, Seth G.; Shumake, Jason D.; Beevers, Christopher G.
ABSTRACT: Attentional bias and self-referential schemas have been observed in numerous cross-sectional studies of depressed adults and are theorised to maintain negative mood. However, few longitudinal studies have examined whether maladaptive cognition predicts the course of depressive symptoms. Fifty-seven adults with elevated depression symptoms were assessed for negative attentional bias using a dot-probe task with eye-tracking and self-referential schemas using a self-referent encoding task. Participants subsequently completed five weekly depression symptom assessments. Participants with more negative self-referential schemas had higher baseline depression symptoms ( r  = .55). However, participants who spent more time attending to negative words showed greater symptom worsening over time ( r  = .42). The findings for negative self-referential schemas replicate past research, while the findings for negative attention bias represent the first evidence showing that attentional biases predict naturalistic symptom course. This work suggests that negative attention biases maintain depression symptoms and represent an important treatment target for neurocognitive therapeutics.